Comparative Mechanical and Thermal Properties of Epoxy Matrix Composite Reinforced with Coco Peat and Coconut Shell Charcoal Fillers for Automotive Brake Friction Applications - Al Ichlas Imran; Nanang Endriatno; Januar Parlaungan Siregar; Mohd Ruzaimi Mat Rejab; Sambodo Arif Wibowo; Tezara Cionita; Deni Fajar Fitriyana (Automotive Experiences, 2025)
Developing epoxy-based composites reinforced with natural materials has become a significant concern in supporting friction materials and sustainable automotive industries. Coco peat and coco shell charcoal are coconut wastes that have the potential as natural fillers to support the mechanical properties of friction material composites while supporting the reduction of biomass waste. This study aims to evaluate the effect of weight fraction variation of coco peat and coco shell charcoal on composite mechanical and thermal properties. Specimens were prepared using the hand lay-up method with 5%, 10%, and 15% filler weight fractions. Mechanical tests were conducted, including tensile test, bending test, Rockwell hardness, and Charpy impact. Results show that the addition of 5% coco peat increased the tensile strength to 28.36 MPa and impact strength to 123.33 J/mÂ², while coco shell charcoal at 10% recorded the highest flexural strength of 36.10 MPa and hardness of 93.66 HRB. However, increasing the filler concentration caused a decrease in tensile and impact strength due to the formation of voids, agglomeration, and micro-cracks. These findings confirm that coco peat is effective for tensile and impact strengthening at low fractions. In contrast, coco shell charcoal improves flexural strength and produces higher hardness values than the commercial brake pad product (59.59-66.90 HRB). Furthermore, the composite with 5% coco shell charcoal showed good thermal stability with a final residue value of 3.83%. Further studies can focus on surface modification of fillers, hybrid composites, and evaluation of tribological properties and the environment to promote applications in the automotive industry sector.